PREGNANCY COURSE AND PERINATAL OUTCOME IN WOMEN WITH PRE-ECLAMPSIA - Sadikova , Hanifa; Eshimbetova, Gulsara; Musakhodjaeva , Diloram (International Journal of Scientific Pediatrics, 2024)
This article discusses the causes and predisposing factors leading to preeclampsia (PE), using the example of the regional perinatal center of the Syrdarya region of Uzbekistan for the period 2020-2022. The purpose of the research: to study the clinical study of the medical history of 5005 birth histories in 2020, 6393 histories in 2021 and 6202 birth histories in 2022, the authors draw conclusions about the causes and predisposing factors of preeclampsia.Research materials and methods:of these, 1277 pregnant women were treated in the PC of the Syrdarya region. Results: An analysis of the case histories of these pregnant women showed that pregnancy is most often complicated by distress of fetus. More than 65% of pregnant women who underwent repeated PE suffered from severe PE, which required early delivery. They often have a history of colds, IDA, and BMI. Newborns from patients with preeclampsia have low Apgar scores. Conclusion: the identified changes require additional study of the problem by obstetrician-gynecologists to determine the pathological mechanisms of fetal PE in women.